Trend of Moral Crisis of Students: A Bibliometric Analyze in Journals of Islamic Education - Khoiriah Khoiriah; Ade Sri Wahyuni; Hasnah Hasnah (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
The moral crisis in education has become a challenge for educators, society, and parents. This article discusses the research findings on students’ moral crises by analyzing articles related to morality in the Journal of Islamic Education in Indonesia. This research employs a qualitative approach using the Systematic Literature Review (SLR) method in six stages: formulation of research questions, search for data, inclusion and exclusion criteria, quality assessment, data collection, and analysis. The primary data in this study consist of articles published in the Science and Technology Index (SINTA) from 2021 to 2024, focusing on morality. These articles are written in either Indonesian or English. Relevant articles as primary data were found on the Garuda Kemendikbud website. Secondary data refers to data gathered from other relevant literature, such as books, theses, and documentation. According to the study results, over the past four years, the number of publications focused on morality has increased. Among these publications, the most common research approach is quantitative, with the research subjects primarily at the Senior High School level. The moral crisis among students is influenced by media, technology, and the family environment. Exposure to inappropriate content and destructive values from social media weakens students’ morals, while disharmony in the family has a negative impact on character development.